2018
DOI: 10.1038/s41598-018-21709-y
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of electrical current distribution to the forced flow and grain refinement in solidified Al-Si hypoeutectic alloy

Abstract: Significant grain refinement in cast metals can be achieved through the application of electric currents during the solidification process. The present paper investigates the distribution of electric currents on the grain size of solidified Al-7wt.%Si alloy under the application of electric current with constant parameters flowing through two parallel electrodes into the melt within a cylindrical mould. The distribution of electric current was controlled by applying an electrical insulation material coating, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
0
19
0
2
Order By: Relevance
“…After using ultrasonic treatment in the solidification process, the grain size of commercial pure aluminum and Al-Si-Cu alloy is greatly refined compared to the alloy without ultrasonic treatment 17,18 . By applying electric and magnetic fields of different strengths during the solidification process, the grains of the Al-Si alloy are also greatly refined 19 . The chemical method mainly refines the grain by adding grain refiner to the aluminum alloy.…”
mentioning
confidence: 99%
“…After using ultrasonic treatment in the solidification process, the grain size of commercial pure aluminum and Al-Si-Cu alloy is greatly refined compared to the alloy without ultrasonic treatment 17,18 . By applying electric and magnetic fields of different strengths during the solidification process, the grains of the Al-Si alloy are also greatly refined 19 . The chemical method mainly refines the grain by adding grain refiner to the aluminum alloy.…”
mentioning
confidence: 99%
“…In addition, the contribution of Joule heating is also not expected to be prominent for the present current density being no more than 67 A•cm −2 since Joule heating is almost negligible for the current density of~120 A•cm −2 in the Al-7Si alloy [20]. During the crystal growth stage, the forced melt flow induced by ECP can induce local fluctuations of both temperature and concentration in the mushy zone and then promote dendrite fragmentation rates, leading to grain multiplication [20,21]. However, the forced convection is insufficient to promote a solutal remelting of dendrite in our case.…”
Section: Resultsmentioning
confidence: 81%
“…Räbiger et al [20] investigated the directional solidification of Al-7Si alloy under rectangular ECP with parallel electrodes and proposed that the formation of fine equiaxed grains was ascribed solely to the electro-vortex flow driven by Lorentz force. Based on the improved experiments, Zhang et al [21] additionally indicated that the forced melt flow promoted dendrite fragmentation rates. From experimental investigation of the relevance of forced melt flow to the solidification structure of pure Al in the mold for embedding the wire mesh under an alternating electric current pulse (AECP) with up-down electrodes, our prior work [22] concluded that melt flow could lead to the columnar fragmentation and make the crystal nuclei on the mold wall fall off and drift in the liquid.…”
Section: Introductionmentioning
confidence: 99%
“…Improving the accuracy requires a significant increase in the number of FEs and corresponding increase in computational time in approximately the same proportion, that is, on conventional processors can reach many hours. Thus, according to [33], for a 3D mesh of 3•10 6 size, the counting time was ~4000 s, for 2D of 5•10 4~1 400 s, 1500-4000 s, and for some tasks a mesh of 443•10 6 FE was reported.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%